Las recaudaciones de naturaleza fiscal en los primeros años del Franquismo - Alejandre García, Juan Antonio (Cuadernos de Historia del Derecho, 2007)
During the Spanish Civil War (1936-1939), the impossibility to apply the fiscal regime that prevailed in republican Spain forced Franco’s government to improvise some imaginative formules to collect taxes; these formules were of a diverse and vague nature but well needed to take care of the numerous problems of social order. This study focuses mainly in the legal norm on which these resources were sustained.